Lifelong Learning and New Competences: A Trans-Disciplinary Study on the Phenomenon of Inactivity in Adult Men - Serena Mazzoli (Pensa MultiMedia, 2024)
The phenomenon of inactivity in adult men, to which we usually refer only for a comparison with traditionally disadvantaged groups, is particularly important for bridging the knowledge gap that characterizes it and for its heuristic value in bringing out prospective indications for an integral human development. The essay confirms the hypothesis of the adult men inactivity, higher in Italy than in other European countries, as a possible condition that negatively affects not only income and family stability, but also the achievement of marketable skills and social awareness. The presentation of a trans-disciplinary study on inactivity in adult men analyses the relationship between object of investigation and the growing interest aroused by issues connected with education for ecological transition. It starts from the heuristic hypothesis according to which sustainability competences could constitute a significant pedagogical driver to respond to the working and social exclusion of the analysed target.